2020
DOI: 10.1016/j.sopen.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anesthesia on the postoperative systemic inflammatory response in patients undergoing surgery: A systematic review and meta-analysis

Abstract: Background Surgical injury stimulates the systemic inflammatory response. The magnitude of the postoperative systemic inflammatory response has been shown to be significantly associated with short and long-term outcomes following surgery of varying severity. Different anesthetic techniques for surgery may have an impact on the postoperative systemic inflammatory response and on the rate of the postoperative infective complications. The aim of the present systematic review was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 82 publications
3
39
0
2
Order By: Relevance
“…This immune response initiates immediately after a surgical injury. Polymorphonuclear leukocytes (PMNs), endothelial cells, macrophages, and lymphocytes are activated by the secretion of pro-inflammatory mediators including cytokines, chemokines, and other molecules including but not limited to reactive oxygen species, nitric oxide, and platelet-activating factor [ 3 ]. While essential, when unchecked, excessive inflammation can disrupt the body's immune system, potentially leading to certain inflammation-related conditions and even organ failure [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This immune response initiates immediately after a surgical injury. Polymorphonuclear leukocytes (PMNs), endothelial cells, macrophages, and lymphocytes are activated by the secretion of pro-inflammatory mediators including cytokines, chemokines, and other molecules including but not limited to reactive oxygen species, nitric oxide, and platelet-activating factor [ 3 ]. While essential, when unchecked, excessive inflammation can disrupt the body's immune system, potentially leading to certain inflammation-related conditions and even organ failure [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Alhayyan et al [ 5 ] in systematic review and meta-analysis reported that it was not clear in the literature whether anesthetic technique has an effect on the magnitude of the postoperative SIR. This was due to the heterogeneity and poor quality of identified studies.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the heterogeneity and poor quality of identified studies. [ 5 ] Furthermore, these authors, in a retrospective audit of the effect of anesthetic technique on the magnitude of the postoperative CRP in patients undergoing elective open or laparoscopic surgery for colon cancer, reported that the magnitude of the postoperative SIR in particular, POD 2 CRP, was modulated by the induction of RA in patients who underwent open surgery, but not laparoscopic surgery for colorectal cancer. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is (2, 6-diisopropyl phenol) is an intravenous general anesthetic, which is extensively used in the induction and maintenance of anesthetization and procedural sedation. Apart from its multiple anesthetic advantages, it has been reported to possess anti-oxidative and anti-in ammatory effects [14,15] as well as neuro-protective properties [16]. A number of in vitro studies revealed that propofol may protect mouse hippocampal neurons from in ammation-induced autophagy [17] and from in ammationand hypoxia-as well as oxidative stress-induced apoptosis [18][19][20].…”
Section: Introductionmentioning
confidence: 99%